1996
DOI: 10.1063/1.871697
|View full text |Cite
|
Sign up to set email alerts
|

Physics of helicon discharges

Abstract: Because of their high density, low-pressure discharges ionized by helicon waves are being studied for their possible use in cluster tools for the fabrication of next-generation computer chips. How helicon waves are related to whistler waves and waves in a plasma-filled waveguide is explained, and the mystery of the high ionization efficiency is outlined. Experimental data on the waves and the equilibrium properties of the discharge are shown, and the status of our current understanding of the physical processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
103
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 17 publications
9
103
0
Order By: Relevance
“…The pressure is measured with a capacitive pressure gauge. As RF antenna a Nagoya-type Helicon antenna which couples to the |m| = 1 Helicon modes is applied [4]. The antenna is connected to the RF generator (13.56 MHz, max.…”
Section: Experimental Setup and Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure is measured with a capacitive pressure gauge. As RF antenna a Nagoya-type Helicon antenna which couples to the |m| = 1 Helicon modes is applied [4]. The antenna is connected to the RF generator (13.56 MHz, max.…”
Section: Experimental Setup and Diagnostic Methodsmentioning
confidence: 99%
“…If the pressure can be reduced, the over-all efficiency of the NNBI system could be increased as the stripping losses of H − due to collisions with the gas would be reduced. Furthermore, more smoother radial profiles of the plasma parameters are expected with Helicon coupling since the coupling mechanism is based on wave heating of the plasma volume [4] not on collisional heating within the skin depth.…”
Section: Introductionmentioning
confidence: 99%
“…The discharge vessel is made out of quartz glass, has a length of 40 cm, a diameter of 10 cm and is attached to the vacuum system at the ends of the cylinder. As RF antenna a Nagoya-type Helicon antenna which couples to the |m| = 1 Helicon modes is applied [11]. The antenna is connected to the RF generator which operates at a frequency of 13.56 MHz via a matching network.…”
Section: Helicon Couplingmentioning
confidence: 99%
“…They reported the surface current required at the boundary of the plasma needed to match the plasma wave field to the vacuum wave field. Chen 12 identified that the surface current was associated with a pseudosurface wave. Chen predicted the existence of pseudosurface waves in a helicon wave device at low B field and a wave propagation mode change between a͒ pseudosurface waves and helicon waves under certain conditions.…”
Section: Introductionmentioning
confidence: 99%